Effect of Occupational Safety, Health (K3) and Leadership Style on Employee Work Productivity Mediated by Discipline in Operations PTPN IV Balimbingan - Hazmanan Khair; R.Sabrina; Rizki Wulanita Batubara (Jurnal Mantik, 2022)
This study aims to determine the effect of occupational health safety (K3) and leadership style on employee work productivity mediated by employee discipline in the operational section of PTPN IV Balimbingan. The research method used is quantitative research, where the variables are measured using a Likert scale. The number of samples in this study was 39 employees of the operational section of PTPN IV Balimbingan. Data collection techniques used in this research are document studies and questionnaires. The data analysis technique used Structural Equation Modeling (SEM) using Smart-PLS. The results of the study indicate that (1) Safety and occupational health (K3) has a significant effect on the work productivity of employees at PTPN IV Balimbingan. (2) Directly safe, occupational health (K3) has a significant effect on employee discipline at PTPN IV Balimbingan. (3) Directly leadership style has a significant effect on employee work productivity at PTPN IV Balimbingan. (4) Directly leadership style has a significant effect on employee discipline at PTPN IV Balimbingan. (5) Directly discipline has a significant effect on work productivity at PT. Nusantara IV Balimbingan Plantation. (6) Indirectly safety, and occupational health (K3) significantly influence work productivity through employee discipline at PTPN IV Balimbingan. In other words, discipline acts as a mediator between occupational safety and health (K3) on work productivity. (7) Indirectly, leadership style has a significant effect on work productivity through the discipline of PTPN IV Balimbingan employees. In other words, discipline acts as a mediator between leadership style and work productivity. This study was only limited by three factors, namely: occupational health safety (K3), leadership style, and discipline. Besides, this study also limits the discipline variable as a mediating variable. Further research can discuss other variables such as motivation, work environment, work ethic, skills, education, and so on. This research is limited only to employees of the operational divisionThis study aims to determine the effect of occupational health safety (K3) and leadership style on employee work productivity mediated by employee discipline in the operational section of PTPN IV Balimbingan. The research method used is quantitative research, where the variables are measured using a Likert scale. The number of samples in this study was 39 employees of the operational section of PTPN IV Balimbingan. Data collection techniques used in this research are document studies and questionnaires. The data analysis technique used Structural Equation Modeling (SEM) using Smart-PLS. The results of the study indicate that (1) Safety and occupational health (K3) has a significant effect on the work productivity of employees at PTPN IV Balimbingan. (2) Directly safe, occupational health (K3) has a significant effect on employee discipline at PTPN IV Balimbingan. (3) Directly leadership style has a significant effect on employee work productivity at PTPN IV Balimbingan. (4) Directly leadership style has a significant effect on employee discipline at PTPN IV Balimbingan. (5) Directly discipline has a significant effect on work productivity at PT. Nusantara IV Balimbingan Plantation. (6) Indirectly safety, and occupational health (K3) significantly influence work productivity through employee discipline at PTPN IV Balimbingan. In other words, discipline acts as a mediator between occupational safety and health (K3) on work productivity. (7) Indirectly, leadership style has a significant effect on work productivity through the discipline of PTPN IV Balimbingan employees. In other words, discipline acts as a mediator between leadership style and work productivity. This study was only limited by three factors, namely: occupational health safety (K3), leadership style, and discipline. Besides, this study also limits the discipline variable as a mediating variable. Further research can discuss other variables such as motivation, work environment, work ethic, skills, education, and so on. This research is limited only to employees of the operational division